Pengaruh Efikasi Diri Dalam Berkarier Dan Impostor Phenomenon Terhadap Pencapaian Karier Pada Mahasiswa Pekerja Di Universitas Pamulang - Naomi Darni Enjolina Laia; Chandra Fitra Arifianto (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract - This study aims to analyze the influence of career self-efficacy and the impostor phenomenon on career achievement among working students at Pamulang University. The research method used is descriptive with a quantitative approach, utilizing primary data obtained through questionnaires. Data analysis includes descriptive statistical tests, instrument tests, classical assumption tests, simple linear regression tests, multiple linear regression tests, correlation coefficient tests (R/Pearson correlation), coefficient of determination tests (R-Square/R2), and hypothesis tests. The partial results show that career self-efficacy has positive and significant influence on career achievement, with a t-value of 7,758, which is greater than the t-table value of 1,980, and a significance level of 0,000, which is less than 0,05. Furthermore, the impostor phenomenon also has a positive and significance level of 0,024, which is less than 0,05. Simultaneously, the results indicate that caree self-efficacy and the impostor phenomenon have a significant influence on career achievement, as shown by the F-value of 35,036, which is grater than the F-table value of 3,07, with a significance level 0,000. The R-Square value of 0,375 indicates that career self-efficacy and the impostor phenomenon explain approximately 37,5% of the variation in career achievement, while the remaining 62,5% is influenced by other factors not examined in this study.